The Influence of Accounting Information Systems in Mediating the Quality of Financial Reports on the Performance of MSMEs in Medan - Galih Supraja (Proceeding of The International Conference on Business and Economics, 2024)
This research aims to determine the Influence of Accounting Information Systems in Mediating the Quality of Financial Reports on the Performance of MSMEs in Medan. The approach used in this research is quantitative, a survey with a Likert scale was distributed to stakeholders interests of MSMEs in Medan. Data analysis carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. Research finds significant effects accounting information systems and the quality of financial reports on the performance of MSMEs. In addition, this research highlights the mediating influence of financial report quality on the relationship between accounting information systems and performance in Medan.